Evaluation of bond strength of self-adhesive resin composite repairs - SILVA,João Victor Gonçalves da (2021)
ABSTRACT Objective: To evaluate the bond strength of repairs with the self-adhering flowable composite Vertise Flow (Kerr) and a conventional composite resin Filtek Z350 (3M ESPE) subjected to different surface treatments. Methods: Forty specimens were divided into four groups: ZV (Filtek Z350 + Vertise Flow, without prior treatment); ZAV (Z350 + Vertise Flow with prior treatment with Single Bond Universal Adhesive System (3M ESPE)); ZAZ (Filtek Z350 + Filtek Z350 with prior treatment with Single Bond Universal Adhesive System (3M ESPE)); VV (Vertise Flow + Vertise Flow, without prior treatment). After 15 days of storage, the specimens were subjected to microtensile tests (Kratos IKCL3-USB, SP, Brazil), with speed of 0.5 mm/min and 20kg load. For statistical analysis, ANOVA with Tukey tests were used (p < 5%). Results: The mean values of the bond strength were highest respectively in the groups: ZV (36.07 ± 37.63); ZAZ (24.04 ± 28.51); VV (19.39 ± 28.24) and ZAV (16.06 ± 15.66). The bond strength of the repairs between the groups presented satisfactory results. Conclusion: The self-adhesive composite resin Vertise Flow seems to be a viable and fast alternative for composite resins repairs.